POST COVID-19 VACCINATION ANXIETY IN MIDWIVES IN MIDWIFERY SERVICES AT INDEPENDENT MIDWIFERY PRACTICE - Putri Puspita Amalia; Budi Prasetyo; Wahyul Anis (Indonesian Midwifery and Health Sciences Journal, 2022)
Abstract Background: Anxiety has been going on during the COVID-19 pandemic and can occur to anyone. Including midwives need to give services with direct physical contact for people who are susceptible to infection. As a solution against the pandemic, the COVID-19 vaccines rapidly developed to reduce the risk of COVID-19 transmission. With the presence of the COVID-19 Vaccines, this study aims to examine the anxiety of midwives after COVID-19 vaccination in midwifery services at IMP (Independent Midwifery Practice). Methods: Descriptive quantitative research with the number of respondents 137 midwives based on total sampling technique. The variable in this study is the level of anxiety measured by the 7-item Coronavirus Anxiety Scale. The data analysis with univariate analysis. Results: Based on the results, it shows of the 137 respondents who have been receiving the COVID-19 vaccine has found 46 respondents (33.6%) with normal category, 55 respondents (40.1%) with mild category, then moderate category as many as 23 respondents (16.8%), and severe category as many as 13 respondents (9.5%). Conclusion: most of the anxiety categories levels experienced are normal until mild. The possible causes are from the visitors who do not apply health protocols and the midwives who have families with susceptible group status. Key words : anxiety, midwives, COVID-19 vaccination